Cuproptosis related genes associated with Jab1 shapes tumor microenvironment and pharmacological profile in nasopharyngeal carcinoma - Wang, Liping; Wang, Dujuan; Yang, Liu; Zeng, Xiaojiao; Zhang, Qian; Liu, Guohong; Pan, Yunbao (Frontiers in Immunology, 2022)
Background: Nasopharyngeal carcinoma (NPC) is the most common subcategory of head and neck squamous cell carcinoma (HNSCC). This study focused on the roles of cuproptosis genes and Jab1 in the tumor microenvironment of NPC and HNSCC. Methods: Differential expression analysis of Jab1 and cuproptosis related genes in tumor cell enriched region (PanCK-expressing) and immune cell enriched region (CD45-expressing) of NPC microenvironment were performed by R software. The limma package was used for the differential analysis. Survival analysis was performed using the survival and survminer packages. Corrplot package was used for correlation analysis. ConsensusClusterPlus package was used for cluster clustering among different regions of NPC, and functional enrichment analysis was performed using GSVA, GSEABase, clusterProfiler, org.Hs.eg.db and enrichplot packages. The pRRophetic package was used to predict drug sensitivity in NPC and HNSCC. Results: Relationships exist between cuproptosis-related genes and Jab1 in the NPC microenvironment. The expression of cuproptosis related genes and Jab1 differed between tumor cell enriched region and immune cell enriched region. AKT inhibitor VIII, Doxorubicin, Bleomycin and Etoposide show higher sensitivity to tumor cell than immune cell. In the high Jab1 group, higher expression of ATP7A, DBT, DLD and LIAS is associated with better prognosis of HNSCC patients. In contrast, in the low Jab1 group, higher expression of these genes is associated with worse prognosis of HNSCC patients. Conclusions: Prognostic cuproptosis related genes and Jab1 provided a basis for targeted therapy and drug development.